Desenvolvimento de sistemas de informação geográfica sob a ótica da qualidade de software - Storck, Marcos André (2006)
The search for the quality of software in the current days became one practical, at least, necessary for the importance of the attributions that we give to them. Each time we depend more and more from software, for the most diverse ends, and thus we become dependents of its exactness. Had to this dependence that the search for the Excellency in software terms became as an act of extreme importance during the development of software. Geographic Information System, or SIG, are software that manipulate data that possess the capacity to have a geographically reference, and due the complexity of these data and the procedures used to manipulate, visualize and process them, the development of SIG becomes a very difficult practical. Studies made on Software Quality, in the area of Software Engineering, had resulted in some methods and techniques that they aim to facilitate the reach of quality during the software development, and, as many times, SIG are developed by professionals from the land areas, these can not have knowledge of such studies on software quality. This work looks for to supply some knowledge on software quality for professionals that are not from computer science area, also considering a methodology that will assist to organize the development process of a SIG, facilitating the reach of the software quality.